The clash of ideologies Middle Eastern politics and American security - Haas, Mark L. (New York ; Oxford : Oxford University Press, 2012)
How do ideologies shape international relations in general and Middle Eastern countries' relations with the United States in particular? This book explores this critical question.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Ideology -- Political aspects -- Middle East; Ideology -- Political aspects -- United States; Middle East -- Foreign relations -- United States; United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- United States -- Case studies; United States -- Foreign relations -- Middle East -- Case studies